PERKEMBANGAN PERMUKIMAN PENDUDUK DI KECAMATAN KURANJI KOTA PADANG TAHUN 2007-2016 - Septia Dwi Risa; Triyatno Triyatno; febriandi febriandi (JURUSAN GEOGRAFI FIS UNP, 2020)
The aims of research are (1) to know land use change of settlements area in Kuranji for 2007 to 2016, (2) the pattern of settlements in Kuranji, (3) the influence of population growth on the development of area of settlements. The type of this research is descriptive quantitative by using land use map of 2007 and 2016, population data of 2007 and 2016. The analysis techniques that used are the overlay of map land use at 2007-2016, nearest neighbor analysis, linear regression analysis. Based on the research show that : (1) land use change of settlements area are 226,56 hectares. Kuranji is the highest settlement of land developments. Those are 58,28 hectares (25,72%) and Anduring is the lowest settlement of land developments. Those are 9,47 hectares (4,18%). (2) Based on the nearest neighbor analysis obtained value of T=0,93 (2007) and T=0.95 (2016). They mean the pattern of settlements in Kuranji including random. (3) population growth influence to the development of settlements.Those are 47,9%.